2022
DOI: 10.1088/1361-6587/ac4857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edge biasing on blob dynamics and associated transport in the edge of the J-TEXT tokamak

Abstract: Effects of edge radial electric field Er and Er × B flow shear on edge turbulence and turbulent transport, in particular, on large-scale blobs and blobby transport have been investigated in the positive and negative biasing discharges in the J-TEXT tokamak. The results show that under certain conditions, the positive electrode biasing induces better plasma confinement than the negative biasing. Further studies reveal that in addition to flow shear effects on blob dynamics, the local radial electric field at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Here we will present some common basic features of the edge biasing such as the various radial profiles (plasma density, temperature, potential, radial electric field and its shear, particle flux), fluctuations in density, and k y spectra as a function of mobility of electrons and ions. It is found that these features qualitatively are similar to the experimental results obtained in [9,15,18,22,[24][25][26][27]41]. The time series of the plasma density (⟨n⟩ x,y , where ⟨⟩ x,y indicates radial and poloidal averages) has been shown in figure 1 using D µ = 2 × 10 −3 for Λ b = +160, +64, −64, and −160 volts by blue, orange, green, and red colored lines, respectively.…”
Section: Simulation Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Here we will present some common basic features of the edge biasing such as the various radial profiles (plasma density, temperature, potential, radial electric field and its shear, particle flux), fluctuations in density, and k y spectra as a function of mobility of electrons and ions. It is found that these features qualitatively are similar to the experimental results obtained in [9,15,18,22,[24][25][26][27]41]. The time series of the plasma density (⟨n⟩ x,y , where ⟨⟩ x,y indicates radial and poloidal averages) has been shown in figure 1 using D µ = 2 × 10 −3 for Λ b = +160, +64, −64, and −160 volts by blue, orange, green, and red colored lines, respectively.…”
Section: Simulation Resultssupporting
confidence: 81%
“…The edge biasing imposes an external electric field in the radial direction, which reduces the plasma turbulence by turbulence decorrelation mainly via ⃗ E × ⃗ B velocity shear that causes higher zonal flows and reduces the anomalous plasma transport in the edge and SOL regions [10][11][12][13]. Several authors have studied the effect of biasing in the boundary region (edge and SOL regions) experimentally [9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] as well as theoretically/numerically [4,7,[28][29][30][31]. Theoretical/numerical studies of edge biasing are attempted in [30,31] using a finite electron temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power source of the EB system after the upgrade consists of ten modules, each module could provide a voltage of 0-100 V. Therefore, the power source could provide a maximum biasing voltage of ±1000 V and a maximum biasing current of ±600 A between the graphite electrode head and the device vacuum chamber wall. Recently, a wealth of research results have been obtained based on this EB system, including plasma rotation modulation [31,32], magnetohydrodynamic (MHD) control [33], plasma confinement improvement [21], deceleration blobs [34] and high density experiments [35] etc. In this paper, the electrode head is inserted into the plasma by a reciprocating pneumatic system in the whole discharge period, and the inner surface of the electrode head stays at r = 22.5 cm (3 cm inside the limiter position).…”
Section: Methodsmentioning
confidence: 99%